Memory and Its Entanglements: A Psychoanalytic Meditation on Terror and Aftermath. Issue 1 (31st December 2022) - Mahon, Eugene
ABSTRACT: The global psychological impact of the events of September 11, 2001 are extremely difficult to measure statistically, and impossible for any one researcher to accomplish successfully. The narrower focus that the study of a few cases can offer, while less ambitious, can find, perhaps in depth, what it lacks in scope. In that spirit, this essay focuses on four individuals, two children and two adults and their distinctly individual reactions. One finding of such an impressionistic study is that it is quite difficult to separate the impact of one specific trauma from other developmental or psychoanalytic factors, which will come as no surprise to students of development or psychoanalysis. That said, the four individuals studied in this essay manage trauma in their own unique ways, suggesting that while trauma can challenge and impinge on character it cannot anticipate the resilience that redresses it with as many strategies as there are individual minds to deploy them. The four clinical descriptions in this essay emphasize this point in a graphic manner.